'Becoming knowledgeable': Ingold's 'wayfaring' and the 'art of translation' as a politics of difference. (2nd October 2021) - Harding, Sue-Ann
ABSTRACT: Anthropologist Tim Ingold has developed powerful ideas about ethical ways of being in the world. Centred on 'becoming knowledgeable' through the continuous practice of 'wayfaring', or 'lineal movement along paths of travel' (Ingold, 2011a, p.149), Ingold's ideas are a call for finding ways to live and act responsively and ethically with our human and other-than-human environments. This essay argues that these interdisciplinary ideas are also powerful for translation scholars and students, particularly as means of dispelling problematic obsessions with 'culture' and 'difference'. It translates the concepts of 'wayfaring', 'making', 'the art of inquiry' and 'making present' into five lines of thought, offered as paths for others to follow. Throughout these strands, as in Ingold's thinking, run the concepts of 'emergent difference' and 'variation in commoning'. Mindful particularly of students, the essay – itself an aspirational act of 'commoning' or an 'imaginative effort to cast my experience in ways that can join with yours (Ingold, 2011a, p.4) – offers ways to conceptualise Ingold's 'art of translation' through ethical practices of attention and correspondence.